Sugar production from wheat straw biomass by alkaline extrusion and enzymatic hydrolysis - Coimbra, Michelle Cardoso [UNESP] (2016)
One characteristic necessary to make ethanol production from biomass economically feasible is to optimize enzymatic dosage, since enzymes production is expensive. This work investigated the efficacy of different enzymes dosages and solid loadings on wheat straw enzymatic hydrolysis, aimed at obtaining process conditions that lead to good sugars yields from pretreated material. Alkaline extrusion was employed as pretreatment at 70 degrees C and 10% NaOH solution (w/v). Enzymatic hydrolysis was performed at 5, 10, 15 and 20% solids loading (w/v). Enzyme doses ranged from 6.92 to 20 FPU/g of glucan. Cellulase was also supplemented with xylanase at various proportions. Alkaline extrusion provided a substrate easier to hydrolyze than untreated material. Even the assay with the lowest enzyme dosage (6.92 FPU) achieved a good carbohydrate hydrolysis yield in relation to the theoretical; the glucose yield was 73.8% and xylose yield was 82.8%. A medium containing 100 g/L of fermentable sugar was obtained at 20% solids loading (w/v) and 20 FPU/g of glucan. The supplementation of cellulase with xylanase at U to FPU activity ratio of 3.11:1 improved the glucose yield about 21% over the assay with no xylanase. (C) 2015 Elsevier Ltd. All rights reserved.